Understanding Behavioral Economics: A Narrative Perspective - Sijabat, Rosdiana (Asian Development Policy Review, 2018)
According to the traditional economics approach, an individual’s decisions reflect that individual’s best interests and are made rationally. Behavioral economics, a field of economics that integrates economics and psychology in analyzing human behavior, is important for explaining why individuals’ decisions and behaviors may not reflect their best interests. A review of the literature has found that behavioral economics has significance for its power to explain individual psychological aspects of the economic decision-making process, both among individuals and institutions. The key methodological approaches deployed to write this article are desktop and library research. On the basis of the literature being reviewed, this article aims to investigate the factors that have increased interest in behavioral economics, and define the key elements of behavioral economics, its application in the public and private sectors, and criticism of behavioral economics. The discussion in this article claims that behavioral economics benefits economics by incorporating other social sciences and approaches in individual behavior and decision making.